2019
DOI: 10.3389/fmars.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Assessment of Marine Litter and Microplastic Ingestion by Cold-Water Coral Reef Benthos at the East Mingulay Marine Protected Area (Sea of the Hebrides, Western Scotland)

Abstract: The extent of marine litter and microplastic occurrence across ocean biomes and species remains poorly characterised, particularly in remote deep-water ecosystems. The present study in the East Mingulay Special Area of Conservation (a Marine Protected Area in the Sea of the Hebrides, western Scotland) used historic surveys and benthic samples to obtain baseline levels of anthropogenic debris and microparticle ingestion. Most debris identified in the MPA was fisheries-related. A total of 11% of benthic macrofau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…One aspect of the plastic problem are microplastics that are most commonly defined as small plastic particles 1 µm-5 mm in size 4 . Microplastics are of particular environmental concern because they are bioavailable to a wide range of marine organisms and are present in food webs [5][6][7][8] . The Arctic Ocean was considered free of plastic pollution until recently, but in the last years the number of publications reporting microplastics in the Arctic waters, sea ice, sediments and biota have been increasing [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…One aspect of the plastic problem are microplastics that are most commonly defined as small plastic particles 1 µm-5 mm in size 4 . Microplastics are of particular environmental concern because they are bioavailable to a wide range of marine organisms and are present in food webs [5][6][7][8] . The Arctic Ocean was considered free of plastic pollution until recently, but in the last years the number of publications reporting microplastics in the Arctic waters, sea ice, sediments and biota have been increasing [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…Madrepora oculata, form a network of calcium carbonate skeletons consisting in branches of multiple corallites built by individual polyps. Macro-and microplastics have been reported in remote deep-sea coral provinces (La Beur et al, 2019) and macroplastic films have been observed to partially obstruct CWC reefs as they can be trapped in the corallite branches (Angiolillo et al, 2015). In short-term experiments (2.5 months), macroplastics were recently shown to impact the growth and prey capture rates, therefore, effecting colony health and survival of L. pertusa (Chapron et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigated the concentration of microplastics in wild-caught invertebrates, from bivalves in Oregon (Baechler, Granek, Hunter, & Conn, 2019) and southeastern India (Naidu, 2019), to deep-sea invertebrates in the northeast Atlantic (Courtene- Jones, Quinn, Ewins, Gary, & Narayanaswamy, 2019) and around the world (Jamieson et al, 2019), to coral reefs in the South China Sea (Ding et al, 2019), Australia (Jensen, Motti, Garm, Tonin, & Kroon, 2019), and cold-water corals off the coast of Scotland (La Beur et al, 2019). Wang, Wang, Ru, and Liu (2019) measured the abundance and characteristics of microplastics found in sediments and benthic organisms from the South Yellow Sea, China, and documented 1.7-47.0 particles per gram (ww).…”
Section: Invertebratesmentioning
confidence: 99%